Non-visualization of fetal gallbladder in microarray era – a retrospective cohort study and review of the literature. (18th August 2019) - Sagi-Dain, Lena; Singer, Amihood; Hadid, Yarin; Sharony, Reuven; Vinkler, Chana; Bar-Shira, Anat; Segel, Reeval; Ben Shachar, Shay; Maya, Idit
Abstract: Objective: The objective of this study is to examine the frequency of abnormal Chromosomal Microarray (CMA) analyses among fetuses with isolated non-visualization of fetal gallbladder. Methods: Data from CMA analyses performed due to isolated non-visualization of fetal gallbladder between January 2013 and September 2016 were retrospectively acquired from a computerized database of the Israeli Ministry of Health. The results were compared with the rate for clinically significant CMA findings in general population, based on a large cohort of 5541 pregnancies undergoing CMA due to maternal request, and a systematic review of 9272 cases with normal ultrasound. Results: Of 45 pregnancies with isolated non-visualization of fetal gallbladder, CMA testing yielded one (2.22%) gain-of-copy-number variant at 16p11.2, categorized as "pathogenic". In addition, one finding of unknown significance was demonstrated. The risk for clinically meaningful CMA findings among pregnancies with isolated absent gallbladder was not significantly increased compared to control population. Conclusions: To the best of our knowledge, this study is the first report describing the rate of pathogenic CMA results in fetuses with isolated non-visualization of fetal gallbladder. The results, in conjunction with previous studies, show that the risk for abnormal CMA results in pregnancies diagnosed with non-visualized gallbladder is not significantly different from pregnancies with normal ultrasound.